Effect of Immigration on Depression among Older Natives in Western Europe - José J. Escarce; Lorenzo Rocco (Institute of Labor Economics (IZA), 2019)
To our knowledge, no study has examined the effect of immigration on the health of older natives. We use the Study of Health, Ageing and Retirement in Europe (SHARE) to investigate whether immigration affects depression among natives 65-80 years old. Immigration may increase the supply and lower the price of personal and household services, a term that refers to care services and non-care services such as cleaning, meal preparation, and domestic chores. Higher consumption of personal and household services by older natives may help maintain health through a variety of pathways including reduced loneliness, greater participation in meaningful social activities, and improved physical functioning. Using a shift-share IV, we find a beneficial effect of immigration on reducing the number of depression symptoms and the probability of clinically significant depression among older natives. We also find some evidence for the hypothesized mechanisms, although our ability to come to definitive conclusions about mechanisms is limited in our data.
Keywords: I12; I14; J61; 330; health; immigration; aging; social determinants